The tipping point : how little things can make a big difference. - Gladwell, Malcolm, ....- (London : Abacus, 2009)
Why did crime in New York drop so suddenly in the mid-nineties? How does an unknown novelist end up a bestselling author? What makes TV shows like Sesame Street so good at teaching kids how to read? Why did Paul Revere succeed with his famous warning? In this brilliant and groundbreaking audiobook, New Yorker writer Malcolm Gladwell looks at why major changes in our society so often happen suddenly and unexpectedly. Ideas, behavior, messages, and products, he argues, often spread like outbreaks of infectious disease. Just as a single sick person can start an epidemic of the flu, so too can a few fare-beaters and graffiti artists fuel a subway crime wave, or a satisfied customer fill the empty tables of a new restaurant. These are social epidemics, and the moment when they take off, when they reach their critical mass, is the Tipping Point. Gladwell introduces us to the particular personality types who are natural pollinators of new ideas and trends, the people who create the phenomenon of word of mouth. He analyzes fashion trends, children's television, and the early days of the American Revolution for clues about making ideas infectious, and visits market mavens and great salesmen to show how to start and sustain social epidemics. The Tipping Point is an intellectual adventure story and a road map to change, with a profoundly hopeful messagethat one imaginative person applying a well-placed lever can move the world.